Non-Linear Viscoelasticity of Rubber Composites and Nanocomposites Influence of Filler Geometry and Size in Different Length Scales - Ponnamma, Deepalekshmi; Thomas, Sabu.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
Origin of Non-Linear Viscoelasticity in Filled Rubbers: Theory and Practice.- Non-Linear Viscoelasticity in Zero Dimensional Filler Reinforced Rubber Composites and Nanocomposites.- Non-Linear Viscoelasticity of One Dimensional Filler Reinforced Rubber Composites and Nanocomposites.- Non-Linear Viscoelastic Studies in Rubber Composites and Nanocomposites-Effects of two Dimensional Fillers.- Non- Linear Viscoelasticity in Rubber Blend Composites and Nanocomposites.- Effect of Hybrid Fillers in the Non-Linear Viscoelasticity of Rubber Composites and Nanocomposites.- Effect of Double Networking on Non-Linear Viscoelasticity of Elastomers.- Modeling of Non-Linear Viscoelastic Behavior of Filled Rubbers.- Effects of Aging on Non-Linear Viscoelasticity.- Rheology of Soft Styrene Butadiene Based Semisolid Rubber Composites.
Origin of Non-Linear Viscoelasticity in Filled Rubbers: Theory and Practice -- Non-Linear Viscoelasticity in Zero Dimensional Filler Reinforced Rubber Composites and Nanocomposites -- Non-Linear Viscoelasticity of One Dimensional Filler Einforced Rubber Composites and Nanocomposites -- Non-Linear Viscoelastic Studies in Rubber Composites and Nanocomposites-Effects of two Dimensional Fillers -- Non- Linear Viscoelasticity in Rubber Blend Composites and Nanocomposites -- Effect of Hybrid Fillers in the Non-Linear Viscoelasticity of Rubber Composites and Nanocomposites -- Effect of Double Networking on Non-Linear Viscoelasticity of Elastomers -- Modeling of Non-Linear Viscoelastic Behavior of Filled Rubbers -- Effects of Aging on Non-Linear Viscoelasticity -- Rheology of Soft Styrene Butadiene Based Semisolid Rubber Composites.
Keywords: Polymers .; Ceramics; Glass; Composites (Materials).; Composite materials; Condensed matter; Polymer Sciences; Ceramics, Glass, Composites, Natural Materials; Condensed Matter Physics